Building pharmacist-patient relationships : a thesis presented in partial fulfillment of the requirements for the degree of Master of Education (Adult Education) at Massey University, Palmerston North, New Zealand - Harries, Diane (Massey University, 2007)
Relationships between pharmacists and patients have become more important with the adoption of patient-centred care in the provision of healthcare in New Zealand. Competence standards for communication and relationship building, which have been introduced for pharmacists, highlight the importance of continuing professional development for best practice. This study explored how pharmacists built relationships with patients and how communication skills training might contribute to this process. A quantitative survey method including both closed and open questions was used to elicit the views of pharmacists and this was analysed using an interpretive process. Pharmacists were found to build relationships using a friendly and respectful approach with appropriate questioning and listening techniques and checking for understanding. It took time to build relationships, but they were seen as essential. Learning to build relationships happened during everyday practice over time. Focused study with experiential methods was seen as helpful by some respondents, although transfer of this learning to practice in real life was found to be challenging. The literature supported these findings including the recognition of difficulty with implementing changes into practice.
Keywords: New Zealand; Pharmacist and patient; Communication in pharmacy